Tract(atus) 23: Theory Is Waiting - Grelet, Gilles; Brassier, Ray (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Gilles Grelet Title (French): Tract(atus) 23: Theory Is Waiting Translated by (French to English): Ray Brassier Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 109 Page Count: 1 Citation (English): Gilles Grelet, “Tract(atus) 23: Theory Is Waiting,” translated from the French by Ray Brassier, Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 109.